2004
DOI: 10.1002/bjs.4751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extra-anatomic bypass grafting with angioplasty for atherosclerotic disease of the supra-aortic trunks

Abstract: Extra-anatomic bypass for supra-aortic trunk disease has a better patency than angioplasty, with a comparable complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…In a nonrandomized comparison of endovascular revascularization with extra-anatomic bypass surgery for subclavian stenosis, all bypass grafts remained patent except 1 that occluded 19 years after operation. 692 In contrast, 6 of 46 attempted subclavian artery angioplasties could not be completed because of occlusive lesions. Among the arteries successfully opened, the 4-year patency rate was 82%.…”
Section: Revascularization Of the Brachiocephalic And Subclavian Artementioning
confidence: 99%
See 1 more Smart Citation
“…In a nonrandomized comparison of endovascular revascularization with extra-anatomic bypass surgery for subclavian stenosis, all bypass grafts remained patent except 1 that occluded 19 years after operation. 692 In contrast, 6 of 46 attempted subclavian artery angioplasties could not be completed because of occlusive lesions. Among the arteries successfully opened, the 4-year patency rate was 82%.…”
Section: Revascularization Of the Brachiocephalic And Subclavian Artementioning
confidence: 99%
“…No randomized trials have compared these methods with surgical revascularization, but numerous reports from single institutions have provided data about early and long-term results, and 2 reports compared results of catheter-based and surgical revascularization in patients with symptomatic obstructive subclavian artery e512 Stroke August 2011 disease. 692,694,695 In a series of 110 patients reported in 2005, the procedure was considered initially successful in 93% of cases. 694 In 6% of cases, total occlusion of the subclavian artery precluded cannulation.…”
Section: Revascularization Of the Brachiocephalic And Subclavian Artementioning
confidence: 99%
“…The endovascular management of atherosclerotic stenoses of SAT has been suggested as an option with low morbidity. However, the medium and long term outcomes of this technique seems to be inferior than the extra-anatomic bypass [8]. In addition, the patient described above, we believe that the refractory angina was a high risk factor for the realization of endovascular treatment.…”
Section: Discussionmentioning
confidence: 88%
“…The extra-anatomic bypass of SAT performed via transsternal revascularization is associated with good late results, with acceptable levels of morbidity and mortality [7][8][9]. In the case described in this article, the bypass of the ascending aorta was performed to both common carotid arteries inserting Dacron graft.…”
Section: Discussionmentioning
confidence: 99%
“…In addition it is sometimes difficult to negotiate a very tight stenosis or occluded lesion through an endovascular approach and the long term benefits of these therapies are uncertain. Modarai et al [7] reported a better patency and lower complication rate related to extra-anatomic bypass for SAT disease as compared to percutaneous endovascular intervention. In this series of 76 patients, with a mean follow up of 5 years, the extra-anatomic graft patency was 97% with no complications against 82% patency for the endovascular intervention with angioplasty with a rate of complication of 11%.…”
Section: Discussionmentioning
confidence: 99%